Labels matter: Use and non-use of 'anti-vax' framing in Australian media discourse 2008–2018. (December 2021) - Court, Jay; Carter, Stacy M.; Attwell, Katie; Leask, Julie; Wiley, Kerrie
Abstract: Childhood vaccine refusal is a globally contentious topic, with some jurisdictions addressing it with punitive policies. Media discourse influences how solutions are framed by implying blame – a process known as framing. We examined Australian media discourse on vaccine rejection over a period in which mandatory childhood vaccination policies were discussed and introduced, focusing on the common Australian pejorative term 'anti-vaxxer'. We mapped frequency of use from January 2008 to December 2018. We then searched Factiva for print media articles on childhood vaccination and parents published in that period, searching separately for articles using and not using 'anti-vaxxer' and variants. We constructed a set of 85 articles that did, and 85 articles date-matched that did not use the term to make comparisons and conducted a frame analysis of each set. 'Anti-vaxxer' was absent in Australian media discourse 2008–2010, rising to a peak of 247 articles using the term at the height of legislative change in 2017. Parents were framed as: 1) deviant "others"; 2) ignorant and in need of informing; 3) vulnerable and in need of protection from anti-vaccination activists; 4) thoughtful, critical, informed, and in need of agency and respect; 5) entitled, privileged and selfish; and finally, 6) lacking access to vaccination, rather than being unwilling. Articles using 'anti-vax' terms were more likely to negatively characterise non-vaccinating parents, while articles not including this language were more likely to frame them as thoughtful or lacking access. This study clearly demonstrates strategic use of pejoratives in the Australian mass media around a time of pressure for legislative change and conflation of anti-vaccination activists with non-vaccinating parents. We suggest fundamental changes to how non-vaccination is framed and dealt with in the media to curb polarization and fostering more respectful dialogue, and better social and public health outcomes. Highlights: Australian media framing of vaccine rejection is mostly pejorative. Frames rarely differentiate non-vaccinators from anti-vaccine activists. Use of pejorative terms increased at a time of pressure for stricter vaccine policy.